Security engineering for cloud computing approaches and tools - Rosado, David G.; Mellado, Daniel; Fernández-Medina, Eduardo; Piattini, Mario 1966- (Premier reference source, 2013)
"This book provides a theoretical and academic description of Cloud security issues, methods, tools and trends for developing secure software for Cloud services and applications" - Provided by publisher